2014
DOI: 10.4088/jcp.14m09081
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Low- and High-Dose Cariprazine in Acute and Mixed Mania Associated With Bipolar I Disorder

Abstract: Objective: This phase 3 trial evaluated the efficacy, safety, and tolerability of low-and high-dose cariprazine in patients meeting DSM-IV-TR criteria for acute manic or mixed episodes associated with bipolar I disorder.Method: This multicenter, randomized, double-blind, placebo-controlled, parallel-group, fixed/flexible-dose study was conducted from February 2010 to December 2011. Patients were randomly assigned to placebo, cariprazine 3-6 mg/d, or cariprazine 6-12 mg/d for 3 weeks of double-blind treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 21 publications
1
96
0
4
Order By: Relevance
“…A limitation of these comparisons across studies is of course that their populations may be quite diverse in terms of demographics and inclusion and exclusion criteria. In addition, the NNT of 5 for remission in this study 1 compares favorably to a pooled NNT of 8 for all atypical agents estimated by another meta-analysis conducted by Tamayo et al 9 Furthermore, Citrome 10 recently reported effect size metrics of different atypical antipsychotics compared to cariprazine with NNT values versus placebo for response and remission. The NNTs for response of 5 in this trial and 7 in a phase 2 study 3 are similar to those observed with other compounds including lithium (NNT = 4), divalproex extended release (NNT = 7), carbamazepine extended release (NNT = 4), olanzapine (NNT = 5), risperidone (NNT = 4), quetiapine extended release (NNT = 6), ziprasidone (NNT = 7), aripiprazole (NNT = 5), and asenapine (NNT = 8).…”
supporting
confidence: 73%
“…A limitation of these comparisons across studies is of course that their populations may be quite diverse in terms of demographics and inclusion and exclusion criteria. In addition, the NNT of 5 for remission in this study 1 compares favorably to a pooled NNT of 8 for all atypical agents estimated by another meta-analysis conducted by Tamayo et al 9 Furthermore, Citrome 10 recently reported effect size metrics of different atypical antipsychotics compared to cariprazine with NNT values versus placebo for response and remission. The NNTs for response of 5 in this trial and 7 in a phase 2 study 3 are similar to those observed with other compounds including lithium (NNT = 4), divalproex extended release (NNT = 7), carbamazepine extended release (NNT = 4), olanzapine (NNT = 5), risperidone (NNT = 4), quetiapine extended release (NNT = 6), ziprasidone (NNT = 7), aripiprazole (NNT = 5), and asenapine (NNT = 8).…”
supporting
confidence: 73%
“…RGH‐MD‐31 (NCT00488618)7 and RGH‐MD‐32 (NCT01058096)8 were flexible‐dose studies with cariprazine 3‐12 mg/d; RGH‐MD‐33 (NCT01058668)6 was a fixed/flexible‐dose study with 2 cariprazine treatment arms (3‐6 mg/d or 6‐12 mg/d).…”
Section: Methodsmentioning
confidence: 99%
“…Detailed methods of the included studies have been previously published 6, 7, 8, 9, 10, 11. Briefly, each study had a washout period of up to 1 week, followed by 3 weeks (bipolar mania studies) or 6 weeks (schizophrenia studies) of double‐blind treatment and a 2‐week safety follow‐up period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently published results of a randomized, double-blind, placebocontrolled study suggests that adjunctive cariprazine 2-4.5 mg/d is effective and generally well tolerated in adults with major depressive disorder who had inadequate responses to standard antidepressants (Durgam et al, 2016a). Positive results have been also obtained from phase II and III clinical trials for bipolar mania (Calabrese et al, 2015;Durgam et al, 2016b;Sachs A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT et al, 2015) leading to approval by the FDA of cariprazine also for the treatment of manic or mixed episodes associated with bipolar disorder (McCormack, 2015). Table S3 reports clinical trials currently running or recently completed regarding cariprazine in different CNS diseases.…”
Section: Accepted Manuscriptmentioning
confidence: 99%